Sensory nerve paresthesia following third molar surgery: Effectiveness of an evidence based protocol - Mohanavalli Singaram; Venkesana Balakrishnaraja Krishnakumararaja; Sasikala Balasubramaniam; Elavenil Paneerselvam; Poornima Poornima; Gayathri Gopi (Wolters Kluwer Medknow Publications, 2014)
Objective: To assess the incidence of inferior alveolar and lingual nerve paresthesia following third molar surgeries and to assess the effectiveness of a set departmental protocol for reducing the incidence of these paresthesia. Study Design: The study included 110 patients who underwent surgery for third molar removal. All cases followed a protocol which included using a standard Ward's incision, raising a lingual flap, use of minimal ostectomy and tooth sectioning in all cases. A standardized data form was used to record the patient's age, sex, Pederson's difficulty index, distance between the root apices and inferior alveolar canal, the length of the "redline" and operating time. Results: Postoperative inferior alveolar nerve paresthesia occurred in five cases (4.5%) and lingual nerve paresthesia occurred in one case (0.9%). Paresthesia was significantly related to the duration of the surgical procedure, but unrelated to the other variables recorded. Conclusion: The current protocol followed appears to be effective in reducing the incidence of inferior alveolar and lingual nerve paresthesia to an acceptable level even in the presence of high risk factors.